ANALISIS TUGAS DINAS PEMUDA OLAHRAGA DAN PARIWISATA DALAM PENGEMBANGAN OBJEK WISATA DANAU RAJA DI KABUPATEN INDRAGIRI HULU - R. Sah Agum R; Adlin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
Activities in the tourism sector are complex activities covering various sectors and forms of activity that have dynamic elements and develop according to the times. Lake Raja is one in Indragiri Hulu Regency which is a natural panorama that has the potential to be developed into a tourism object. However, this tourist attraction looks less than optimally managed, such as scattered garbage and poor road access and destroying the beauty of the natural panorama.The purpose of this research is to find out the implementation of the tasks of the Youth, Sports and Tourism Office in the Development of Raja Lake Tourism Objects in Indragiri Hulu Regency. And to find out the inhibiting factors in the implementation of the Tasks of the Tourism Office in the Development of Raja Lake Tourism Objects in Indragiri Hulu Regency?The method used in this research is a qualitative research method. Data obtained directly from informants using interviews and other data to support research. Data collection techniques were carried out by means of interviews, observation and documentation. This study uses a descriptive analysis technique. After the data is collected completely and thoroughly.Based on the results of the research that the author did, the development of the Raja Lake tourist attraction carried out by the agency was seen from a fairly diverse tourist attraction, which was a tourist attraction in the form of a saung that resembled a traditional house and the agency built supporting facilities and infrastructure so that visitors felt comfortable and returned. again visited the Lake Raja tourist attraction, but in this modernization era the department did not develop enough in the field of promotion and marketing through social media. The obstacles experienced by the Department of Tourism and Culture of Inhu Regency in developing the Lake Raja tourist attraction are the lack of Human Resources, low awareness of the local community, lack of careful planning in planning development.  Keywords: Analysis, Tasks, Tourism Object Development